Лексико-семантичні засоби реалізації конфронтаційної стратегії комуніканта-об'єкта примирення - Передон, Наталія Олександрівна; Peredon, Nataliia O. (Дрогобицький державний педагогічний університет імені Івана Франка, 2017)
Стаття присвячена дослідженню комунікативної поведінки об’єкта примирення (мовця, який є постраждалою внаслідок конфлікту стороною). Виокремлено та проаналізовано основні лексико-семантичні засоби, за допомогою яких цим учасником комунікативної ситуації "примирення" реалізується конфронтаційна стратегія. The focus of the article is to explore the communicative behaviour of the interlocutor who has suffered from the conflict situation and is the object of the initiative for reconciliation. The author has made an attempt to determine and analyze the main lexico-semantic means implementing the confrontation strategy of the object’s of reconciliation speech behaviour. It has been concluded that in order to refuse the initiator’s request for restoring harmonious relations the object of reconciliation uses the following lexico-semantic means: personal and social invectives which aim at expressing negative attitude to the initiator of reconciliation and his maleficent deed, as well as humiliating his dignity and mental abilities; utterances containing the inverted assessment of initiator’s qualities; etiquette forms of address which serve to express the abrupt change of the politeness levels and thus manifest the estrangement and restraint between the interlocutors as a result of the conflict; imperatives which are mainly used in exclamatory sentences to express the unwillingness to forgive the initiator of reconciliation. The imperatives in the speech of the object of reconciliation also demonstrate his intention to stop communicative interaction with the initiator of reconciliation.
Lexico-Semantic Means of Expressing the Confrontation Strategy of the Interlocutor Who Is the Object of Reconciliation
Keywords: конфронтаційна стратегія; негативно маркована лексика; ініціатор примирення; об’єкт примирення; confrontation strategy; lexical items with negative connotation; initiator of reconciliation; object of reconciliation